2009
DOI: 10.1590/s0021-75572009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Púrpura trombocitopênica idiopática na infância: estudo de base populacional no Catar

Abstract: The study revealed a high incidence of ITP among children in Qatar. The study findings are in line with other international reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
1
4
0
2
Order By: Relevance
“…On the other hand, Glanz et al in Colorado [17] -similar to this study -showed an equal distribution of genders. As for the age distribution, this study was similar to those in Iraq, Qatar, and King Khalid University Hospital [11][12][13].…”
Section: Demographicssupporting
confidence: 78%
See 3 more Smart Citations
“…On the other hand, Glanz et al in Colorado [17] -similar to this study -showed an equal distribution of genders. As for the age distribution, this study was similar to those in Iraq, Qatar, and King Khalid University Hospital [11][12][13].…”
Section: Demographicssupporting
confidence: 78%
“…This study differed from other studies in gender distribution. Locally and regionally, it showed an almost equal distribution of genders in contrast to male predominance in a study by Al-Mulla et al in Qatar (62% male) [12] and in a study by Al Fawaz in King Khalid University Hospital (61% male) [13], which contrasts to the female predominance seen in Abha (41% male) [14]. Internationally, there was male predominance in a study by Grainger et al in UK hospitals (57% male) [15], while Zeller et al in Norway [16] showed female predominance (43% male).…”
Section: Demographicsmentioning
confidence: 73%
See 2 more Smart Citations
“…São de extrema importância também a confirmação da ausência de outras condições clínicas que causem trombocitopenia, como infecções, doenças autoimunes, neoplasias e efeito adverso de medicamentos. Não existe exame laboratorial para o diagnóstico 2,3,4,5,6 . O tratamento difere de acordo com a idade e gravidade do paciente, sendo que o prognóstico de PTI em adultos é muito distinto do infantil e tende a forma crônica na maioria dos casos.…”
Section: Introductionunclassified